Analyzing Foreign Policy: the Dynamics of U.S., Türkiye, and Israel's Engagement in Syria - Dewi, Dyah Apriliana Chandra; Pedrason, Rodon; Perwita, Anak Agung Banyu (East Asian Journal of Multidisciplinary Research, 2024)
This paper examines the foreign policy strategies and motivations of the United States, Turkey, and Israel in relation to Syria, providing a nuanced comprehension of the intricate geopolitical landscape. The research employs a qualitative-descriptive methodology to analyze the strategic objectives and actions of these nations, relying on secondary data from scholastic articles and reports. The analysis encompasses the Syrian conflict from 2011 to the present, emphasizing critical variables including national security interests, geopolitical ambitions, and humanitarian considerations. Significant implications for international relations and regional stability are revealed by the findings, which indicate that policy objectives are distinct yet overlapping.